SWI/SNF Complexes Containing Brahma or Brahma-Related Gene 1 Play Distinct Roles in Smooth Muscle Development - Zhang, Min (American Society for Microbiology, 2011)

(untitled)
SWI/SNF ATP-dependent chromatin-remodeling complexes containing either Brahma-related gene 1 (Brg1) or Brahma (Brm) play important roles in mammalian development. In this study we examined the roles of Brg1 and Brm in smooth muscle development, in vivo, through generation and analysis of mice harboring a smooth muscle-specific knockout of Brg1 on wild-type and Brm null backgrounds. Knockout of Brg1 from smooth muscle in Brg1(flox/flox) mice expressing Cre recombinase under the control of the smooth muscle myosin heavy-chain promoter resulted in cardiopulmonary defects, including patent ductus arteriosus, in 30 to 40% of the mice. Surviving knockout mice exhibited decreased expression of smooth muscle-specific contractile proteins in the gastrointestinal tract, impaired contractility, shortened intestines, disorganized smooth muscle cells, and an increase in apoptosis of intestinal smooth muscle cells. Although Brm knockout mice had normal intestinal structure and function, knockout of Brg1 on a Brm null background exacerbated the effects of knockout of Brg1 alone, resulting in an increase in neonatal lethality. These data show that Brg1 and Brm play critical roles in regulating development of smooth muscle and that Brg1 has specific functions within vascular and gastrointestinal smooth muscle that cannot be performed by Brm.